1992
DOI: 10.1016/0014-5793(92)80697-f
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and characterization of human endothelial nitric oxide synthase

Abstract: The constitutive calcium/calmodulin-dependent nitric oxide (NO) syn~hasc cxprcsscd in vascular endothclium shams common biochcmjcal and pharmacologic properties with ncuronal NO synthasc. However. rcccnl cloning und molecular charaacrizalion of NO synthase from bovine endothclial cells indicated the existence of a family of constitutivo NO synlhascs. Accordingly, we undertook molecular cloning and scqucncc analysis of human cndothelial NO synthasc. Complemcruary DNA clones prcdicl a protein of 1,203 amino acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
184
0
6

Year Published

1993
1993
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 455 publications
(194 citation statements)
references
References 19 publications
4
184
0
6
Order By: Relevance
“…Cell Culture-Human umbilical vein endothelial cells (HUVEC) were cultured in M199 (Invitrogen) containing 20% fetal bovine serum (Hyclone, Logan, UT), 17 units/ml heparin, and 0.05 mg/ml endothelial mitogen (Biomedical Technologies Inc., Stoughton, MA), as described previously (17). VSMC and human dermal microvascular endothelial cells (MVEC), purchased from Clonetics (Cambrex, East Rutherford, NJ), were cultured as recommended by the supplier.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell Culture-Human umbilical vein endothelial cells (HUVEC) were cultured in M199 (Invitrogen) containing 20% fetal bovine serum (Hyclone, Logan, UT), 17 units/ml heparin, and 0.05 mg/ml endothelial mitogen (Biomedical Technologies Inc., Stoughton, MA), as described previously (17). VSMC and human dermal microvascular endothelial cells (MVEC), purchased from Clonetics (Cambrex, East Rutherford, NJ), were cultured as recommended by the supplier.…”
Section: Methodsmentioning
confidence: 99%
“…To mimic hypoxia, cells were treated with a 140 M concentration of the iron-chelator desferrioxamine (DFO) (Sigma). After treatment, RNA was extracted as described previously (17).…”
Section: Methodsmentioning
confidence: 99%
“…All the surface cysteines (Cys 93, Cys 98, Cys 211, Cys 234, and Cys 381) were identified as sites of S-nitrosylation in our studies, except for Cys 200. In the reductase domain, we have found that regions containing cysteine-660, À801, and À1113 are known to bind with FMN, FAD, and NADPH (Mardsen et al, 1992). Other sites found to undergo S-nitrosylation (cysteines 852, 975=990, and 1047=1049) have not been implicated in any known biochemical functions.…”
Section: Determination Of S-nitrosylation Sites In Enos Treated With mentioning
confidence: 99%
“…It is synthesized from Endothelial NOS (eNOS), also known as nitric oxide synthase 3 (NOS3) or constitutive NOS (cNOS), is an enzyme that in humans is encoded by the NOS3 gene located in the 7q35-7q36 region of chromosome 7 [13]. Nitric oxide (NO) is an important protective molecule in the vasculature, and endothelial NO synthase (eNOS) is responsible for most of the vascular NO produced.…”
Section: Nitric Oxidementioning
confidence: 99%